The effect of preschool on the school performance of children from immigrant families. Results from an introduction of free preschool in two districts in Oslo - Nina Drange; Kjetil Telle (Statistics Norway, Research Department, 2010)
Two districts of Oslo started to offer five-year-old children free preschool four hours a day. We analyze the effect of this intervention on the school performance of the children from immigrant families 10 years later (age 16). Our difference-in-difference approach takes advantage of the variation caused by the intervention being implemented in two districts in Oslo, leaving other similar districts unaffected. The grade point average of girls increases substantially more in the intervention districts than in the comparison districts; resulting in an effect estimate of more than a quarter of a standard deviation. There is no significant change in boys' performance, and no support for disadvantageous effects on non-cognitive outcomes.
Keywords: J13; J15; H52; I28; 330; preschool; immigrants; early intervention; school performance